PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PEMBELAJARAN TEMATIK TERPADU KELAS IV - Dayu Putri Bareno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the improvement of learning outcomes by implementing PBL model to the integrated thematic learning. This was qualitative and quantitative research. The type of this research was PTK. The research was conducted at SDN 52 Parupuk Tabing, Padang. The technique used in this research was observation, test, and non-test. The results obtained that the percentage of the RPP observation in Cycle I was 90.62% and it increased in Cycle II to 96.87%. After that, the percentage of the teacher aspect in Cycle I was 71.42% and it increased in Cycle II to 96.42%. Then, the aspects of students also increased from 75% in Cycle I to 92.85% in Cycle II. This study also revealed that 8 people had a prominent attitude in Cycle I and Cycle II. Moreover, the average score of knowledge in Cycle I was 65.14 and increased in Cycle II to 88.25. The average score of the skill aspect in Cycle I was 65.14 and increased to 88.25 in Cycle II. This proved that PBL model improved the learning process and the students’ learning outcomes.